Agonist-induced Actin Polymerization Is Required for the Irreversibility of Platelet Aggregation - Torti, Mauro; Tolnai Festetics, Enrico; Bertoni, Alessandro; Sinigaglia, Fabiola; Balduini, Cesare (Thrombosis and Haemostasis, 1996)
Cytochalasin D was used to investigate the role of intracellular cyto-skeleton in the stabilization of platelet aggregation induced by strong platelet agonists. Incubation of gel-filtered platelets with increasing concentrations of cytochalasin D resulted in a dose-dependent inhibition of actin polymerization and association of actin-binding proteins with the Triton X-100-insoluble material induced by the thromboxane analogue, U46619, and the thrombin receptor activating peptide, TRAP. The same concentrations of cytochalasin D did not significantly inhibit platelet aggregation promoted by the two agonists. The addition of the chelating agent EDTA to fully aggregated platelets, that had been treated with cytochalasin D, resulted in the rapid and almost complete disaggregation. EDTA did not cause disaggregation of control, solvent-treated, aggregated platelets. The degree of platelet disaggregation induced by EDTA was dependent on the dose of cytochalasin D used, and was correlated with the inhibition of the cytoskeletal reorganization. Aggregation of cytochalasin D-treated platelets stimulated with U46619 or TRAP was also reverted by the addition of the tetrapeptide RGDS or the fibrinogen y-chain dodecapeptide, which competitively interfere with fibrinogen binding to the glycoprotein Ilb-IIIa complex. These results indicate that the intracellular cytoskeleton plays an essential role in the stabilization of the fibrinogen-platelet interaction, and is necessary for the irreversibility of platelet aggregation induced by strong agonists.